A Case Report of Implantation of the Multifocal Intraocular Lens in a Patient with Marfan’s Syndrome - Shukhaev, S. V.; Petrosyan, Yu. M.; Mordovtseva, E. A. (Oftalmologii͡a, 2024)
Purpose: To demonstrate a case report of successful implantation of multifocal IOL in patients with Marfan syndrome. Materials and methods. A young patient with Marfan’s syndrome asked to the clinic. Examination revealed ectopia of the lens in both eyes. Given his active lifestyle and the desire to get rid of glasses, he was offered surgical treatment with implantation of a multifocal IOL. Lens phacoemulsification was performed with implantation of a modified capsular tension ring, and a trifocal IOL (PanOptix) in the bag. Results. In the late postoperative period, the maximum corrected visual acuity for near in the right eye was 0.9, in the left — 0.8; for the average distance — 0.7 on both eyes; for the distance on the right eye — 1.0, on the left — 0.8. Conclusion . This clinical case demonstrated that in some cases, ectopia of the lens in Marfan syndrome is not a contraindication to the implantation of a multifocal IOL.